2021
DOI: 10.1055/s-0041-1727576
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Burnout, and Coping among First-Year Medical Undergraduates

Abstract: Background and Objectives Stress, burnout, and coping have been found to be interlinked with each other. Several adverse psychological outcomes have been associated with stress and burnout. Improving coping can decrease the stress and burnout. There is limited literature on perceived stress, coping, and burnout among first-year medical undergraduates from India. With this background, the study aimed to assess perceived stress, coping, and burnout among first-year medical undergraduates. Methods It was a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Results of this study indicated that stress has a positive effect on academic burnout in the online learning process of medical students, indicating that it is one of the important risk factors of academic burnout, and the occurrence of academic burnout should be avoided by regulating students' stress in online learning; thus, H1a was supported. This finding was in line with prior studies which confirmed that stress was interlinked with academic burnout among medical students [e.g., (66)(67)(68)]. Guruprakash et al (66) pointed out that after experiencing great stress, medical students would show painful emotions and have relatively higher scores for burnout.…”
Section: The Correlation Between Stress Social Support Resilience And...supporting
confidence: 90%
“…Results of this study indicated that stress has a positive effect on academic burnout in the online learning process of medical students, indicating that it is one of the important risk factors of academic burnout, and the occurrence of academic burnout should be avoided by regulating students' stress in online learning; thus, H1a was supported. This finding was in line with prior studies which confirmed that stress was interlinked with academic burnout among medical students [e.g., (66)(67)(68)]. Guruprakash et al (66) pointed out that after experiencing great stress, medical students would show painful emotions and have relatively higher scores for burnout.…”
Section: The Correlation Between Stress Social Support Resilience And...supporting
confidence: 90%
“…By the results of our study, we argue, that there are no personal problems, and there is no stress in first-year male medical students compared to second-year students. Seems first-year stress is more associated with stressful learning and not with any personal problems as revealed in previous publications cited in the section introduction (Guthrie, et al, 1997;Moffat, McConnachie, Ross, & Morrison, 2004;Nowreen & Ahad, 2019;Damiano et al, 2021;Nebhinani, Kuppili, & Mamta, 2021).…”
Section: Discussionsupporting
confidence: 51%
“…On a personal level, this stress can diminish one's capabilities and the importance of a future profession (Dyrbye, Thomas, & Shanafelt, 2005;Guthrie, et al, 1997;Moffat, McConnachie, Ross, & Morrison, 2004;Aktekin et al, 2001). Studies found that the most important stressors related to academic performance and the learning environment (Nowreen & Ahad, 2019;Damiano et al, 2021;Nebhinani, Kuppili, & Mamta, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact prevalence varies amongst reported studies [14], burnout rates of up to 49.6% have been reported for medical students [15][16][17]. Different reports from around the world have found medical student burnout rates of 9.09-62% in Asia [18][19][20][21], 15.05-46% in Europe [22][23][24][25][26], 13-75% in the Middle East [27,28], 49% in North America [29], 12-44.9% in South America [30][31][32], and 20% in New Zealand.…”
Section: Introductionmentioning
confidence: 99%